2015
DOI: 10.1039/c4cc06809b
|View full text |Cite
|
Sign up to set email alerts
|

Air stable NHCs: a study of stereoelectronics and metallorganic catalytic activity

Abstract: The air stable NHC IPrBr is reported. A stereoelectronic study of IPrBr and its similarly stable relative IMesBr demonstrates metal complex specific changes in NHC donicity versus the ubiquitous IPr and IMes. Application to a Suzuki coupling and an iridium transfer hydrogenation gives superior outcomes using IPrBr and IMesBr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…511 Colacino et al 512 reported iridium−NHC conplexes bearing 3,4,5-trimethoxybenzyl Nsubstituents, taking 144a and 144b as examples (Scheme 54).…”
Section: Osmium-based Catalystsmentioning
confidence: 98%
“…511 Colacino et al 512 reported iridium−NHC conplexes bearing 3,4,5-trimethoxybenzyl Nsubstituents, taking 144a and 144b as examples (Scheme 54).…”
Section: Osmium-based Catalystsmentioning
confidence: 98%
“…As reported by Cole and co‐workers, [Pd(IPr Br )(cin)Cl] ( 9 c ) can be prepared in good yield by using the free carbene route . We also prepared [Pd(IPr Cl )(cin)Cl] ( 9 b ) from free IPr Cl .…”
Section: Resultsmentioning
confidence: 72%
“…KO t Bu) . Their corresponding salts were obtained in quantitative yields as previously reported ,. Under inert atmosphere, IPr was reacted with either CCl 4 or CBr 4 for three hours to generate the C 4,5 ‐haloganed carbene and one equivalent of haloform (CHX 3 , X=Cl or Br) .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…. Pd‐complexes (SIMesPd(cinn)Cl, SIPrPd(cinn)Cl and 6MesPd(cinn)Cl, IMesPd(cinn)Cl, IPrPd(cinn)Cl) were prepared according to the literature procedures.…”
Section: Methodsmentioning
confidence: 99%